Law and Society in Transition: Philosophical Reflections on the Dynamics of Justice and Social Change - Anisa, Nur; Budiana, I Nyoman; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The rapid social changes occurring in the modern era place law and society in a dynamic and complex relationship. This study seeks to philosophically analyze the relationship between law and society in the context of ongoing social change, and examines the role of law as both an instrument and a reflection of these social dynamics. This research uses a qualitative approach with a philosophical reflection method on the concepts of justice, norms, and social transformation. The results of the study indicate that law cannot be understood solely as a set of rigid rules, but rather as a historical and cultural product that continues to evolve in line with changing societal values. During periods of social transition, law plays a dual role: on the one hand, it functions as a control instrument to prevent change from causing chaos, and on the other, it acts as a mirror that reflects the aspirations, moral awareness, and demands for justice in society. Philosophically, the relationship between law and society is dialectical—society shapes law, and law, in turn, shapes social behavior. Therefore, justice in the context of a transitional society must be understood dynamically, namely justice that is able to adapt to change without losing its moral foundation. In conclusion, responsive law rooted in social values ​​is a prerequisite for the creation of substantive justice in a constantly changing society.